Coffee and tea intake and risk of Breast Cancer - Pathy, N.B.; Peeters, P.; van Gils, C.; Beulens, J.W.J.; van der Graaf, Y.; Bueno-de-Mesquita, B.; Bulgiba, A.; Uiterwaal, C.S.P.M. (2010)
Known risk factors account for about 10-15 of breast cancer incidence suggesting that lifestyle exposures are crucial in its etiology. Previous epidemiological studies on the association between coffee and tea consumption and breast cancer risk have been inconsistent. We investigated the association of coffee and tea consumption with the risk of breast cancer among women in EPIC-NL cohort, a population-based prospective cohort in Netherlands with 27,323 participants. Exposure was measured by a validated food frequency questionnaire, and the outcome was verified by direct linkage with the Netherlands Cancer Registry. A total of 681 invasive primary breast cancers were diagnosed in 9.6 years of follow-up. Coffee intake increased the risk of breast cancer by more than twofold as compared to non-consumers (HR; 2.25, 95 CI; 1.30-3.90). This association did not hold after multivariate adjustment which resulted in a HR of 1.17, 95 CI; 0.65-2.12. After adjustment to breast cancer risk factors and lifestyle, no association was observed between intake of coffee or tea and risk of breast cancer across all categories of intake. These results were also not altered by body mass index (BMI). Coffee and tea consumption does not seem to be related to the risk of breast cancer in women.